Efforts to Eradicate Criminal Acts of Corruption as an Extraordinary Crime Through International Cooperation - Wilshen Leatemia (JURNAL BELO, 2022)
Corruption is a common enemy that must be eradicated by Indonesia in order to achieve a just and prosperous life. The Indonesian government has made various efforts to eradicate corruption and save state finances. Various products of legislation, institutions, special teams and commissions have been formed by the government to combat corruption to its roots in order to save the economy and state finances. However, corruption is still a problem as an inhibiting factor for the country's economic development. The research was conducted using a normative juridical method with a statute approach and a conceptual approach. Eradication of criminal acts of corruption as an extraordinary crime, because it is serious, systematic and structured, should also be carried out in an extraordinary manner. Extraordinary eradication of criminal acts of corruption is carried out through extraordinary duties and authorities of the Corruption Eradication Commission (KPK), through investigations, investigations and prosecutions carried out in an extraordinary manner by the Corruption Eradication Commission (KPK), development of international cooperation in the context of mutual legal assistance, investigations joint and extradition treaty.